Analisis Tingkat Kebugaran Jasmani Siswa Ekstrakurikuler Pencak Silat SMP N 21 Surabaya - Noni Aprilla; Mochamad Ridwan (Jurnal Keolahragaan, 2026)
Physical fitness plays an important role in supporting students' participation in pencak silat extracurricular activities. Good physical fitness contributes to the mastery of techniques, training performance, and achievement in sports. Therefore, this study was conducted at SMPN 21 Surabaya to determine the level of physical fitness among students participating in the pencak silat extracurricular program using the Tes Kebugaran Pelajar Nusantara (TKPN). The study employed a descriptive approach with a survey test method. A total of 20 students participated in the research and completed several fitness assessments, including Body Mass Index (BMI), V Sit and Reach, 60-second Sit-Up, 30-second Squat Thrust, and the Progressive Aerobic Cardiovascular Endurance Run (PACER). Data were analyzed using descriptive statistics, including mean, frequency, and percentage. The results showed that 85% of the participants were classified in the poor fitness category, while only 15% were classified in the moderate category. The average physical fitness score was 2.15, with a standard deviation of 0.366. Overall, the students' physical fitness levels were predominantly categorized as poor. In general, the findings indicate that the physical fitness level of students participating in the extracurricular program at SMPN 21 Surabaya remains low. These findings can serve as evaluation material for developing more structured, measurable, and sustainable physical training programs.Kebugaran  jasmani  berperan  besar  dalam membantu siswa berpartisipasi dalam kegiatan ekstrakurikuler  pencak silat. Kebugaran jasmani yang  baik  mendukung  penguasaan teknik, performa latihan, dan pencapaian prestasi. Jadi, dilakukan penelitian di SMPN 21 Surabaya untuk melihat seberapa fit mahasiswa yang terlibat dalam Pencak Silat sebenarnya menggunakan tes TKPN. Peneliti menggunakan pendekatan deskriptif dan metode uji survei. Mereka memiliki 20 siswa yang mengikuti berbagai tes kebugaran. Indeks Massa Tubuh (IMT), V sit and reach, sit up dalam 60 detik, squat thrust 30 detik, dan Progressive Aerobic Cardiovascular Endurance Run (PACER). Data dianalisis menggunakan statistik deskriptif berupa rata-rata, frekuensi, dan persentase. Dari semua peserta, 85% termasuk dalam kategori kurang bugar, sementara hanya 15% yang dianggap baik-baik saja. Skor rata-rata untuk kebugaran adalah 2,15, dengan standar deviasi 0,366. Secara keseluruhan, tingkat kebugaran jasmani siswa masih didominasi oleh kategori kurang. Secara umum, hasil penelitian ini menunjukkan kebugaran jasmani siswa ekstrakurikuler di SMPN 21 Surabaya masih kurang. Temuan ini dapat digunakan sebagai bahan evaluasi untuk menyusun program latihan fisik yang lebih terstruktur, terukur, dan berkelanjutan.